Совершенствование системы технического обслуживания автомобилей - Бажинов, Ан. В. (НТУ "ХПИ", 2015)
Предложен энергетический метод управления периодичностью технического обслуживания автомобилей, который заключается в аналитическом методе оценки потребности в запасных частях и принципиально отличается тем, что математическая модель оценки потребности в запасных частях базируется на скорости изнашивания сопряженных силовых агрегатов, учитывающая энергетические затраты на выполнение транспортной работы, а также индивидуальные особенности и техническое состояние конкретной транспортной машины.

An energymanagement method periodical lymaintenance of vehicles, whichisan analyticalmethod for estimating thedemand forspareparts andis fundamentally differentin that themathematicalmodel for evaluatingthe need forsparepartsis based on thewear rateof conjugatedpowertrains,which takes into accountthe energycosts of meeting thetransportoperation, as well as individual characteristicsand condition ofthe particularvehicles.Oneof the most difficultissues is theregular training ofreliable dataon the assessment ofneedsfor spare parts forvehicles.Therefore, the problemof optimal control ofthe needfor spare partsis closely linkedwith the creation ofthe automated complextaskson the storage andanalyticalprocessing of statistical dataon the actualneeds, supply and consumptionof spare partsat all levelsof government.The lack ofcomprehensive, accurate, correctlyreflecting the true stateof informationabout the volume, nomenclature andplaces of storageof spare partsis, as a rule,to the accumulationof excessiveresidues andmakes it impossible forsuppliersto properly evaluatethe need forreplacement parts, reducing the simpletransport vehiclesto be repaired.
Improving the system ofvehicle maintenance
Keywords: топливо; периодичность; метод; пробег; car; fuel; frequency; method; mileage